Functional Bracing After Anterior Cruciate Ligament Reconstructions: A Review of the Current Literature - Charles R. Heyworth; Lauren E. Berube, PA-C; Emma C. Gossman, BS; Matthew D. Milewski, MD; Elise C. Bixby, MD (Journal of the Pediatric Orthopaedic Society of North America, 2025)
Anterior cruciate ligament (ACL) injuries are increasingly common in pediatric and adolescent athletes, driven by rising participation in high-risk sports. Functional knee bracing (FKB) has been proposed as a strategy to reduce both initial injuries and reinjuries following ACL reconstruction (ACLR). The current review examines biomechanical and clinical evidence related to the use of FKB status post-ACLR, focusing on its potential in preventing ACL re-injury. Biomechanical studies suggest that FKB may reduce abnormal knee movements in controlled conditions, specifically anterior tibial translation. However, results are inconsistent on preventing injury-inducing movements or mechanisms in the knee when assessed as part of dynamic testing. Clinically, the small number of relevant comparative studies analyzing braced versus nonbraced cohorts show heterogeneous results, with mixed conclusions on whether FKB effectively reduces ACL re-tear rates. There are several understudied aspects associated with FKB, leaving surgeons without definitive recommendations regarding key factors, such as the optimal brace type, the impact of graft type, appropriate timing and duration of brace wear, compliance challenges, and the psychological and proprioceptive effects of bracing on patients. Given the conflicting evidence and lack of definitive existing guidelines, the role of FKB for patients returning to high-risk activities after ACLR currently remains uncertain, underscoring the need for higher-quality research to guide clinical practice, particularly for the highest risk sub-populations of pediatric and adolescent athletes. Key Concepts: (1) Functional knee braces have been shown to reduce anterior tibial translation in controlled conditions but show inconsistent effects on rotational forces and valgus stability during dynamic activities. (2) Clinical studies offer conflicting evidence on the effectiveness of functional bracing in reducing ACL re-tear rates, with no consensus on routine use. (3) Patient-specific factors, including graft type, compliance, and baseline knee stability, may influence the effectiveness of functional bracing. (4) Psychological benefits, such as reduced fear of reinjury, may contribute to the value of bracing, though effects on proprioception and muscle strength are mixed. (5) Further research is needed, particularly with dynamic, sport-specific testing, to determine the true efficacy of functional bracing in ACL reconstruction recovery.